Can Personalized Tourniquet Systems Prevent Chemotherapy-induced Alopecia? - McEwen, Jim A.; Jeyasurya, Jeswin; Jameson, Michael; Howard, Fuschia; Abadi, Shirin; Simmons, Christine (CMBES Proceedings, 2016)
Alopecia (hair loss) is a common consequence of cancer treatment known to have a profound impact on quality of life. Tourniquet technologies have been investigated from the mid-1960s to early 1980s as a strategy for preventing chemotherapy-induced alopecia (CIA) but their ambiguous results precluded incorporation into any standard of treatment. Our hypothesis is that fundamental advances inherent in personalized tourniquet systems developed within our group over 38 years enables the optimal, safe, comfortable and reliable stoppage of penetration of arterial blood into the scalp during infusion of chemotherapeutic agents, thereby preventing CIA and improving quality of life. This paper describes these advances, and presents options for integration into various treatment protocols involving modern chemotherapeutic agents having differing pharmacokinetics. Personalized tourniquet systems offer significant potential to safely prevent CIA, thereby improving quality of life with low treatment cost and low impact on treatment times and workflow.